Efektivitas Kekuatan Eksekutorial Pada Sertifikat Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Dinda Laras Ayu Pratiwi; Andi Salman Maggalatung; Nurhasanah Nurhasanah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This research contains an analysis of the considerations of the Constitutional Court in deciding the Constitutional Court Decision Number 18/PUU-XVII/2019 and the effectiveness of its implementation. This research uses the juridical-normative method and the legal material comes from the Constitutional Court Decision Number 18/PUU-XVII/ 2019 and other decisions. The results of this research revealed that the decision was based on the principle of justice and legal certainty. The implementation itself has not been going well because there are still several unfulfilled factors.